Uma nova estratégia para renderizar descontinuidades e superfícies intersectantes em modelos baseados em splats - Ivo, Rafael Fernandes (2011)
Splats based models have gained increasing attention due to its potential for rendering complex geometric models efficiently and with high quality. The absence connectivity information of these models allows complex modeling operations, as Boolean operations, and fractures in physics simulations. However, these operations often generate models with edges and corners that can not be represented correctly with a finite number of splats without a treatment to be done. In this work, a neighborhood graph uses an estimate which ensures the connection of all these splats on opposite sides a discontinuity and that need to be clipped against each other. After using a method for detecting discontinuities in the generated graph, the neighbors participating in the a splat clipping, clip partners are determined to cut out and sorted splat so as to adapt it to the curve of discontinuity. Another problem encountered in rendering models based on reconstruction of splats is intersecting surfaces. Close intersections of surfaces, the surfaces are mixed, resulting in artifacts. to treat these cases, a segmentation algorithm performs separation of the various surfaces present in the model, identifying the splats that form and hold them to be combined into areas near the intersections of surfaces in the surface reconstruction phase space image.